Template polymerization - Polowinski, Stefan (ChemTec Pub., 1997)
Template polymerization is a field in polymer synthesis but also common practice in the biosynthesis since DNA is the most popular template or matrix on which proteins are built by living species. This field is relevant to the synthesis of polymers of controlled structure but its application goes beyond the synthesis. Materials are formulated in complex mixtures always containing components that can be regarded as templates on which other materials are formed, modified, or are interacted with. In the product development the relevance of these phenomena is controlled by the order of addition which affects probabilities and preferences of interaction. Introducing the first published monograph devoted to this emerging technology.